2009
DOI: 10.4138/5932
|View full text |Cite
|
Sign up to set email alerts
|

Windsor Group (Late Mississippian) stratigraphy, Magdalen Islands, Quebec: a rare eastern Canadian record of late Visean basaltic volcanism

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…b). The islands are built on Carboniferous–Visean volcanic and sedimentary substrata (Brisebois ; Giles ). The geomorphology of the islands is dominated by basaltic conical hills surrounded by sandstone and shale platforms slightly inclined towards the sea, which are interpreted as cryopediment surfaces (Laverdière & Guimont ; Paquet ).…”
Section: Geological and Geomorphological Settingsmentioning
confidence: 99%
“…b). The islands are built on Carboniferous–Visean volcanic and sedimentary substrata (Brisebois ; Giles ). The geomorphology of the islands is dominated by basaltic conical hills surrounded by sandstone and shale platforms slightly inclined towards the sea, which are interpreted as cryopediment surfaces (Laverdière & Guimont ; Paquet ).…”
Section: Geological and Geomorphological Settingsmentioning
confidence: 99%
“…B). Both islands are composed of Carboniferous−Visean volcanic and sedimentary substrata (Brisebois ; Giles ). The geomorphology of the islands is dominated by basaltic conical hills surrounded by sandstone and shale platforms slightly inclined towards the sea, which are interpreted as cryopediment surfaces (Laverdière & Guimond ; Paquet ).…”
Section: Geological and Geomorphological Settingmentioning
confidence: 99%
“…The methods are largely sensitive to the average of the crustal structure, and thus are insufficient to constrain the details of the evolution, geometry, and structure of the GSL region [ Jackson , ]. Petrological investigations revealed that extensive bodies of Mississippian age volcanic rocks cover the thick column of Paleozoic sedimentary rocks [ Barr et al , ; Keen and Williams , ; Giles , ]. The capping volcanic rocks are associated with local salt tectonism at depth [ Barr et al , ], and they conceal the deeper sedimentary and crustal structures from active seismic profiling such as the reflection and refraction surveys conducted by the oil and gas industry and the Lithoprobe project [e.g., Keen et al ., , ; Voogd and Keen , ; Marillier and Verhoef , ; Marillier et al , ; Hall et al ., , ].…”
Section: Introductionmentioning
confidence: 99%